Toad venom-derived bufadienolides and their therapeutic application in prostate cancers: Current status and future directions - Ye, Qingmei; Zhou, Xin; Han, Fangxuan; Zheng, Caijuan (Frontiers in Chemistry, 2023)
Cancer is the second leading cause of death worldwide. Specially, the high incidence rate and prevalence of drug resistance have rendered prostate cancer (PCa) a great threat to men’s health. Novel modalities with different structures or mechanisms are in urgent need to overcome these two challenges. Traditional Chinese medicine toad venom-derived agents (TVAs) have shown to possess versatile bioactivities in treating certain diseases including PCa. In this work, we attempted to have an overview of bufadienolides, the major bioactive components in TVAs, in the treatment of PCa in the past decade, including their derivatives developed by medicinal chemists to antagonize certain drawbacks of bufadienolides such as innate toxic effect to normal cells. Generally, bufadienolides can effectively induce apoptosis and suppress PCa cells in-vitro and in-vivo, majorly mediated by regulating certain microRNAs/long non-coding RNAs, or by modulating key pro-survival and pro-metastasis players in PCa. Importantly, critical obstacles and challenges using TVAs will be discussed and possible solutions and future perspectives will also be presented in this review. Further in-depth studies are clearly needed to decipher the mechanisms, e.g., targets and pathways, toxic effects and fully reveal their application. The information collected in this work may help evoke more effects in developing bufadienolides as therapeutic agents in PCa.